KOMODITAS PETERNAKAN UNGGULAN DI KABUPATEN CIAMIS - Sri Mulyati; Enok Sumarsih; Rina Nuryati (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
The era of regional autonomy gives authority to regions to manage their own regions, including the utilization of regional potentials in carrying out development. This research was conducted with the aim of identifying livestock commodities which are the base in the sub-district area in Ciamis Regency, knowing the growth of livestock commodities in the sub-district area in Ciamis Regency, and identifying livestock commodities which are the potential ones in Ciamis Regency. The research was conducted from January to September 2020. The research method used was a case study of seven livestock commodities analyzed by SLQ and DLQ and Shift Share analysis. The results showed: (1) The livestock commodities which are the base in the sub-district area in Ciamis Regency are cows, sheep, goats, native chickens, broilers, laying hens, and ducks. (2) The growth of livestock commodities that are experiencing rapid growth are beef cattle and layer and basic livestock commodities that are competitive are beef cattle, sheep, goats, domestic chickens, broilers, layer, and ducks. (3) Animal husbandry commodities which are the potential commodities in Ciamis Regency are beef cattle and layer.